2016
DOI: 10.1186/s12957-016-0820-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiological, and pathological features of 33 adult unilateral thalamic gliomas

Abstract: BackgroundUnilateral adult thalamic gliomas are rarely reported. In this study, the authors aimed to analyze the clinical, radiological, and pathological features of adult primary unilateral thalamus gliomas (UTGs).MethodsClinical data of 33 UTGs in adults who underwent surgical treatment between 2005 and 2014 at the Beijing Tiantan Hospital were collected and retrospectively studied. Follow-up evaluation was performed.ResultsThis study included 21 males and 12 females with a mean age of 43.1 years. The most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
4
18
0
Order By: Relevance
“…Zhang et al studied the clinical, radiological and pathological features of adult unilateral thalamic gliomas. 13 They reported a mean age of 43.1 years in their cohort, almost similar to Aihara et al, who reported a mean age of 38 years. 8 Both these studies have included grades II, III and IV astrocytomas in their analysis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Zhang et al studied the clinical, radiological and pathological features of adult unilateral thalamic gliomas. 13 They reported a mean age of 43.1 years in their cohort, almost similar to Aihara et al, who reported a mean age of 38 years. 8 Both these studies have included grades II, III and IV astrocytomas in their analysis.…”
Section: Discussionsupporting
confidence: 80%
“…The majority of studies so far have analyzed pediatric and adult thalamic gliomas of low and high grades together. Zhang et al studied the clinical, radiological and pathological features of adult unilateral thalamic gliomas . They reported a mean age of 43.1 years in their cohort, almost similar to Aihara et al , who reported a mean age of 38 years .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In large solid lesions, debulking by microsurgery is usually the best, as declared by Zhang et al and Puget et al; in their series, larger resection, whether it was in patients with a low-or high-grade lesions, was associated with better clinical outcome, proving that the extent of resection is an important determinant [3,22]. In large solid lesions planned for microsurgery, MR tractography is usually indicated to assess the feasibility of microsurgery, the designed approach, and the expected morbidity, this was supported by Moshel et al who showed the important role of tractography in choosing and planning the surgical approach through confirming Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Thalamus; 2 cases in Lt. Thalamus Surgery, RT,and CT T. cort STR in 4 cases; PR in 1 case OS was 2 to 20 months 2 Akiyama et al [ 5 ] 18 3 cases in Rt. thalamus; 2 cases in Lt. thalamus; 13 cases in ventricle, putamen, deep part of frontal lobe Surgery (under endoscope), RT, and CT T. cort GTR in 4 cases; STR in 1 case; PR in 3 cases; biopsy in 10 cases Without data of follow-up 3 Zhang et al [ 4 ] 33 19 cases in Rt. thalamus; 14 cases in Lt. thalamus Surgery in 5 cases; surgery and RT.…”
Section: Introductionmentioning
confidence: 99%